2017
DOI: 10.1164/rccm.201605-0912oc
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Rehospitalization at the Same Hospital or a Different Hospital Following Critical Illness

Abstract: Almost one-third of mechanically ventilated critically ill patients were rehospitalized at a different hospital than that of the index ICU stay. This care discontinuity was associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
(47 reference statements)
0
15
0
4
Order By: Relevance
“…May et al reported the outcomes of DHR in patients with critical illness, and they believed that care fragmentation was a possible cause of the poorer outcomes. 21 Sepsis is a complex disease, and sepsis patients are more likely to experience fragmentation of care. As a high-risk group with high in-hospital mortality rate, diagnosis and treatment for sepsis patients may be delayed due to incomplete knowledge of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…May et al reported the outcomes of DHR in patients with critical illness, and they believed that care fragmentation was a possible cause of the poorer outcomes. 21 Sepsis is a complex disease, and sepsis patients are more likely to experience fragmentation of care. As a high-risk group with high in-hospital mortality rate, diagnosis and treatment for sepsis patients may be delayed due to incomplete knowledge of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Повторный перевод (ПП) в ОРИТ -это показатель, который наряду с внутригоспитальной летальностью может рассматриваться как критерий эффективности работы ОРИТ и стационара в целом. С экономической и организационной точек зрения он сопряжен с увеличением работы койки в ОРИТ, ростом затрат стационара на лечение и реабилитацию [1][2][3][4][5][6][7][8][9] и госпитальной летальности [3][4][5][6][7][10][11][12][13][14][15]. Так, после поправки на непредотвратимые факторы риска неблагоприятных исходов среди пациентов, возвращенных в ОРИТ, в 4 раза повышается уровень летальности и в 2,5 раза -длительность пребывания в стационаре [6] с соответствующим ростом стоимости лечения и ухудшением прогнозов.…”
unclassified
“…Так, в США критерием является интервал в течение 48 ч с момента перевода из ОРИТ [17,19]. Такой же период времени часто используют в странах ЕЭС, он указан рабочей группой Европейского общества интенсивной терапии (European Society of Intensive Care Medicine) [2,5,22]; одновременно в других исследованиях оценивается 72-часовая зависимость [23], 30-дневная [9,11,[24][25][26] и пр. В свою очередь каждый временнóй интервал отражает конкретные характеристики отдельных групп факторов риска ПП.…”
unclassified
See 2 more Smart Citations